Evaluation of waste water incineration - A case study at AkzoNobel in Stenungsund - Hallbäck, Maria (My University, 2017)
Waste incineration is an important part of many processes. Waste water incineration is however, not a common practice. This thesis has evaluated the performance of waste water incineration through a case study at AkzoNobel in Stenungsund. The primary aim of the process is the destruction of ammonia present in the waste water and ventilation gas feed streams. Secondary focus is to reduce the formation of NOx in the process. The waste water incineration process consists of two evaporators, one furnace, one dust cyclone, a separation step containing one quench and one separation unit, and lastly one electrostatic filter before the flue gases are emitted to the atmosphere via a flue gas fan and a stack. The evaluation was performed in three parts. The first part included mapping mass balances of the incinerator and the important units. The balances were based on real time data from the process. In the second part a chemical reaction modelling software was used to make a sensitivity analysis for the operating parameters with respect to the NOx formation. The third part consisted of experimental tests varying a set of parameters that were run over a period of around six days. The result of the mapping shows that the mass balance may be completed. The modeling results indicates that the most important parameters are temperature, amount of excess air and amount of water fed to the furnace. The Experimental test results are consistent with both literature and modeling outcome. The conclusion from this thesis work is that high temperature and high oxygen levels yields a low ammonia slip but increase the amount of NO formed. On the other hand, low temperatures and low oxygen levels gives low levels of NO but increase the amount of un-reacted ammonia in the stack. The flow of direct water also has a large effect on the performance of the furnace. The most important uncertainties are the ventilation gas composition and the amount of ammonia washed away in the quench step.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering